Professional identity development: learning and journeying together - Bridges, Stephanie J. (Elsevier, 2017)
Background: Pharmacy students start to develop their professional values through engagement with the course, practice exposure, staff and fellow students. Group working is an element of pedagogy which draws on the social aspects of learning to facilitate knowledge and skills development, but its potential role in facilitating professional identity formation has as yet been under researched. Objectives: This study aimed to explore the potential of mutual learning through group work to contribute not only to academic knowledge and understanding, but also to the development of students’ professional values and selves. Methods: Semi-structured interviews were conducted with 17 home and international first year undergraduate pharmacy students in a UK School of Pharmacy, to explore their experiences of interacting for learning with other students on the course. Findings: Thematic analysis of the interview data highlighted four main benefits of mutual learning, which are that it: promotes friendly interactions; aids learning about the subject and the profession; opens the mind through different opinions and ways of thinking; and enables learning about other people. Through working together students developed their communication skills and confidence; reflectively considered their own stance in the light of others’ experiences and healthcare perspectives; and started to gain a wider worldview, potentially informing their future interactions with patients and colleagues. Some difficulties arose when group interactions functioned less well. Conclusions: Opportunity for collaboration and exchange can positively influence development of students’ professional outlook and values. However, careful management of group working is required, in order to create a mutually supportive environment wherein students feel able to interact, share and develop together.